Revealed Notions of Distributive Justice II – Experimental Evidence - Nicole Becker; Kirsten Häger; Jan Heufer (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
We report the results of a combination of a dictator experiment with either a 'social planner' or a 'veil of ignorance' experiment. The experimental design and the analysis of the data are based on the theoretical framework proposed in the companion paper by Becker, Häger, and Heufer (BHH, 2013), in which we introduce a 'notion of distributive justice' by which individuals trade off equality and efficiency. The purpose of the theoretical framework is to explain preferences in dictator experiments by a combination of selfishness and concerns for distributive justice. Most participants conform very well with the Agreement and Symmetry axioms proposed in BHH; we find that for 80% of participants the evidence is very strong. The experiment therefore demonstrates that most participants' behaviour in dictator experiments can be explained by a combination of selfishness and concerns for distributive justice. We also provide a rough classification of preferences and notions of distributive justice and show that participants' strength of the sense for justice (Karni and Safra 2002b) can be compared nonparametrically. – – Wir stellen die Ergebnisse aus einem Diktator Experiment kombiniert mit entweder einem Sozialen Planer Experiment oder einem Experiment hinter dem Schleier des Nichtwissens vor. Das experimentelle Design und die Analyse der Daten basieren auf dem theoretischen Ansatz aus dem Begleitpapier von Becker, Häger, und Heufer (BHH 2013), in dem wir eine "Gerechtigkeitsvorstellung" einführen mit der Individuen Gleichheit und Effizienz abwägen. Die Idee des theoretischen Konstrukts liegt darin, Präferenzen im Diktator Experiment durch eine Kombination aus Eigennutz und einer Vorstellung von Verteilungsgerechtigkeit zu erklären. Die meisten Teilnehmer stimmen mit den Agreement und Symmetrie Axiomen die in BHH vorgestellt wurden überein; wir stellen fest, dass die Evidenz für 80% der Teilnehmer sehr stark ist. Das Experiment demonstriert daher, dass das Verhalten von den meisten Teilnehmern in Diktator Experimenten durch eine Kombination aus Eigennutz- und Verteilungsgerechtigkeit erklärt werden kann. Wir nehmen ebenfalls eine grobe Klassifikation der Präferenzen und Gerechtigkeitsvorstellungen vor und zeigen, dass sich die Stärken des Sinnes für Gerechtigkeit (Karni und Safra 2002b) der Teilnehmer nichtparametrisch vergleichen lassen.
Keywords: C14; C91; D11; D12; D63; D64; 330; altruism; dictator games; distributive justice; experimental economics; nonparametric analysis; preference decomposition; revealed preference; social preferences